Early and post transition metal complexes as a single of combined components in the ethylene and isoprene polynerization - Furlan, Luciano Gomes (2005)
In this work is reported, in a first step, the effect of different experimental parameters and their relation with polymer properties using the homogeneous binary catalyst system composed by Ni(α-diimine)Cl2 (α-diimine = 1,4-bis(2,6-diisopropylphenyl)- acenaphthenediimine) and {TpMs*}V(Ntbu)Cl2 (TpMs* = hydridobis(3-mesitylpyrazol-1- yl)(5-mesitylpyrazol-1-yl)) activated with MAO. This complexes combination produces, in a single reactor, polyethylene blends with different and controlled properties dependent on the polymerization temperature, solvent and Nickel molar fraction (xNi). In second, the control of linear low density polyethylene (LLDPE) production was possible, using a combination of catalyst precursors TpMsNiCl (TpMs = hydridotris(3- mesitylpyrazol-1-yl)) and Cp2ZrCl2, activated with MAO/TMA, as Tandem catalytic system. The catalytic activities as well as the polymer properties are dependent on xNi. Polyethylene with different Mw and controlled branches is produced only with ethylene monomer. Last, the application group 3 metals catalysts based, M(allyl)2Cl(MgCl2)2.4THF (M = Nd, La and Y), in isoprene polymerization with different cocatalysts systems and experimental parameters is reported. High yields and polyisoprene with good and controlled properties were produced. The metal center, cocatalysts and the experimental parameters are determinant for the polymers properties and their control. High conversions in cis-1,4- or trans-1,4-polyisoprene were obtained and the polymer microstructure depending of cocatalyst and metal type. Combinations of Y and La precursors were effective systems for the cis/transpolyisoprene blends production, and the control of cis-trans-1,4-microstructures by Yttrium molar fraction (xY) variation was possible.